Pengaruh Populasi Ikan Lele Dan Jenis Media Tanam Terhadap Pertumbuhan Dan Hasil Tanaman Bayam (Amaranthus Sp.) Pada Sistem Akuaponik - Ridwan Ridwan; Hudaya Mulyana; Lia Sugiarti (OrchidAgro, 2021)
This study aims to study the interaction between catfish populations and the type of growing media on the growth and yield of spinach (Amaranthus sp.) Cultivated by the aquaponics system. This research was conducted using an experimental method (experiment), from July to August 2020 in the experimental area of the PUSKOPAD complex, Tanjungsari District, Sumedang Regency. at an altitude of 850 m above sea level. The experimental design used was the Split Plot Design with the basic design of the RAK. Which consists of 2 factors with 2 repetitions. The first factor or mainplot is the catfish population (i) which consists of 4 levels, namely: (i1) = 0 tails, (i2) = 10 tails, (i3) = 20 tails, (i4) = 30 tails. The second factor or subplot is the type of planting medium (m) which consists of 4 types, namely: (m1) = Rockwool, (m2) = Oyster mushroom waste, (m3) = husk charcoal, (m4) = Pumice stone. Based on the results of experiments regarding the influence of catfish populations and the type of growing media on the growth and yield of spinach grown in the aquaponic system. That there was an interaction between the treatment of catfish populations and the type of planting medium on the parameters of the observation of plant height at 20 days after planting (DAS) and 30 DAS and leaf number at 10 DAS and 35 DAS. The use of pumice growing media is best used for the cultivation of spinach in an aquaponic system and a population of 20 catfish is sufficient to provide the nutrient needs needed by spinach plants.